ANALISIS IMPLEMENTASI SISTEM PROTEKSI AKTIF DAN PASIF, SARANA PENYELAMATAN JIWA DAN PENGORGANISASIAN KEBAKARAN DI PROYEK PERKERETAAPIAN STASIUN MANGGARAI PT. X TAHUN 2021 - Elisabeth Kristina Ari Nugrahanti (2022)
Fire is a condition when a building in a certain place is exposed to fire and later can cause casualties and other losses. The DKI Jakarta Province Sectoral Statistics Portal reported that in 2020, 1,505 fire cases that occurred in DKI Jakarta Province. Previously, this project has seen a fire case. Beside that, various activities in the project, such as welding work, can pose a risk of fire. The purpose of this study was to analyze the implementation of a fire protection system as an effort to prevent fires at the Manggarai Station Railway Development Project by comparing the applicable standards such as Permen PU No.26/PRT/M/2008, Permenakertrans No. Per.04/MEN/1980, SNI_03_1745_2000, SNI 03-3985-2000, SNI 03-3989-2000, SNI 03-6570-2001, SNI 03-6571-2001, SNI 03 - 1736 - 2000, SNI 03 - 1746 - 2000, SNI 03-6574-2001, NFPA 101, and Permen PU No. 20/PRT/M/2009. This study used descriptive qualitative method. The results of this study indicate that there is still a mismatch in the application of the fire protection system with applicable standards. The only active protection system that applied in this project is fire extinguishers. The average application of active protection systems is 13%, passive protection systems 80%, life saving facilities 96.2%, and fire organization 91.6%. Recommendation for this project is to add various active protection systems that are not available, make adjustments to one of the entrances to make it 6m wide, and add a floor warden in fire organization.